POTENSI SARGASSUM SEBAGAI IMUNOSTIMULAN PADA BIDANG AKUAKULTUR (REVIEW) - MUAHIDDAH, NURI; DWIYANTI, SEPTIANA (Universitas Mahasaraswati K. Mataram, 2024)
The aquaculture industry continues to grow, but its production encounters problems, one of which is disease outbreaks that can hinder the growth and sustainability of fish production. Research on the use of immunostimulants as an environmentally friendly solution to enhance the resilience of aquatic organisms against diseases is becoming increasingly important. One natural substance that can be used as an immunostimulant is Sargassum seaweed, a type of brown algae found abundantly in tropical and subtropical waters. This study aims to present a recent review of the potential of Sargassum as an immunostimulant in the field of aquaculture. Thisalgae is known to contain various bioactive compounds, including polysaccharides (alginate and fucoidan), polyphenols, and natural pigments, which are believed to have the ability to enhance the immune response of aquatic organisms. Its application has been tested both in vitro and in vivo. The addition of extracts from various types of Sargassum can be done through injection, immersion, or adding them to the feed of cultured organisms. Extracts from several types of Sargassum have been proven to enhance the immune system, growth, and survival of aquatic organisms, as well as to combat disease outbreaks. The application of Sargassum as an immunostimulant is an environmentally friendly solution to combat disease outbreaks